Feasibility of oral microbiome profiles associated with oral squamous cell carcinoma - Kengo Hashimoto; Dai Shimizu; Sei Ueda; Satoru Miyabe; Ichiro Oh-Iwa; Toru Nagao; Kazuo Shimozato; Shuji Nomoto (Journal of Oral Microbiology, 2022)
Objective Recently, the possibility that oral microbiomes is associated with oral squamous cell carcinoma (OSCC) initiation and progression has attracted attention; however, this association is still unclear. Here, we comprehensively analyze the microbiome profiles of saliva samples using next-generation sequencing followed by determining the association between oral microbiome profiles and OSCC.Materials and Methods Microbiome profiles in saliva samples from patients with OSCC, oral leukoplakia (OLK), and postoperative OSCC (Post) were analyzed. Candidate OSCC-associated bacteria were identified by comparing the bacterial diversity and relative abundance of each group based on these microbiome profiles, and their applicability as OSCC detection tools were evaluated.Results There were significant differences in genus abundances (Streptococcus, Aggregatibacter, and Alloprevotella) among the groups from saliva samples. In the OSCC group, compared with the OLK and Post groups, abundances of the genus Fusobacterium, phylum Fusobacteria and phylum Bacteroidetes were markedly increased and that of the genus Streptococcus and phylum Firmicutes were decreased.Conclusion The results suggested a strong association of these bacteria with OSCC. Especially, phylum Fusobacterium was significantly associated with early recurrence of OSCC. Thus, oral microbiome analysis may have a potential of novel OSCC detection and prognostic tool.